2018
DOI: 10.1186/s13075-018-1594-z
|View full text |Cite
|
Sign up to set email alerts
|

Pannus inflammation in sacroiliitis following immune pathological injury and radiological structural damage: a study of 193 patients with spondyloarthritis

Abstract: BackgroundThe pathogenesis of sacroiliitis is unclear; therefore, we aimed to systematically study the immunopathology of sacroiliitis in patients with axial spondyloarthritis (axSpA), and explore the relationship between pannus formation, inflammation, and the structural damage caused by sacroiliitis.MethodsFine needle aspiration biopsy of the sacroiliac joint (SIJ) was performed in 193 patients with axSpA. Clinical, laboratory, and imaging data were collected at baseline and during the follow up. Immunohisto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…K trans , K ep and V e parameters re ect perfusion and permeability,the reverse transportation of gadolinium chelate back to the vascular space as well as extravascular extracellular space volume.In the present study,there were no signi cant differences between the model group and control group based on DCE-MRI parameters assessing in the joint space of SIJ at 12 weeks after induction.These results were consistent with the pathological results which showed no signi cant positive in ammatory changes at 12 weeks. At 17 and 22 weeks,the differences of K trans between the two groups were statistically signi cant.The previous investigations have noted that in early stages of axial SpA, pannus formation helps in understanding the associated pathological changes [25] .It is characterized by formation of high vascular granulation tissue by the in amed synovium and/or subchondral bone marrow.In ammation may subsequently trigger the formation of angiogenesis by increasing the density of the micro-vessels that provide a channel for expression of mediation and invasion of in ammatory cells and this in turn exacerbates local damage to the cartilage [26/27] .Based on pathological results,local in ltration of in ammatory tissues of the subsynoviocytic and areolar connective tissue in the early stage may led to the increase of vascular permeability. A related view is that François R J et al [28] have reported that a small number of lymphocytes and plasma cells with a large number of macrophages in ltrated the subsynoviocytic and areolar connective tissue in a systematic histological study of early SIJ.…”
Section: Discussionmentioning
confidence: 99%
“…K trans , K ep and V e parameters re ect perfusion and permeability,the reverse transportation of gadolinium chelate back to the vascular space as well as extravascular extracellular space volume.In the present study,there were no signi cant differences between the model group and control group based on DCE-MRI parameters assessing in the joint space of SIJ at 12 weeks after induction.These results were consistent with the pathological results which showed no signi cant positive in ammatory changes at 12 weeks. At 17 and 22 weeks,the differences of K trans between the two groups were statistically signi cant.The previous investigations have noted that in early stages of axial SpA, pannus formation helps in understanding the associated pathological changes [25] .It is characterized by formation of high vascular granulation tissue by the in amed synovium and/or subchondral bone marrow.In ammation may subsequently trigger the formation of angiogenesis by increasing the density of the micro-vessels that provide a channel for expression of mediation and invasion of in ammatory cells and this in turn exacerbates local damage to the cartilage [26/27] .Based on pathological results,local in ltration of in ammatory tissues of the subsynoviocytic and areolar connective tissue in the early stage may led to the increase of vascular permeability. A related view is that François R J et al [28] have reported that a small number of lymphocytes and plasma cells with a large number of macrophages in ltrated the subsynoviocytic and areolar connective tissue in a systematic histological study of early SIJ.…”
Section: Discussionmentioning
confidence: 99%
“…At 17 and 22 weeks,the differences of K trans between the two groups were statistically significant. The previous investigations have noted that in early stages of axial SpA, pannus formation helps in understanding the associated pathological changes [ 25 ]. It is characterized by formation of high vascular granulation tissue by the inflamed synovium and/or subchondral bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…K trans , K ep and V e parameters re ect perfusion and permeability,the reverse transportation of gadolinium chelate back to the vascular space as well as extravascular extracellular space volume.In the present study,there were no signi cant differences between the model group and control group based on DCE-MRI parameters assessing in the joint space of SIJ at 12 weeks after induction.These results were consistent with the pathological results which showed no signi cant positive in ammatory changes at 12 weeks. At 17 weeks, the K trans , K ep and V e values in the model group were higher than those of the control group.However, only the differences of K trans between the two groups were statistically signi cant.The previous investigations have noted that in early stages of axial SpA, pannus formation helps in understanding the associated pathological changes [19] .It is characterized by formation of high vascular granulation tissue by the in amed synovium and/or subchondral bone marrow.In ammation may subsequently trigger the formation of angiogenesis by increasing the density of the micro-vessels that provide a channel for expression of mediation and invasion of in ammatory cells and this in turn exacerbates local damage to the cartilage [20/21] .Based on pathological results,local in ltration of in ammatory cells of the subsynoviocytic and areolar connective tissue in the early stage may led to the increase of vascular permeability. A related view is that François R J et al [22] have reported that a small number of lymphocytes and plasma cells with a large number of macrophages in ltrated the subsynoviocytic and areolar connective tissue in a systematic histological study of early SIJ.…”
Section: Discussionmentioning
confidence: 99%